Understanding leadership experiences: the need for story sharing and feminist literature as a survival manual for leadership - Lord, Linley; Preston, Alison (Routledge, 2009)
This paper uses an auto-ethnographic storytelling approach to connect an individual's experience in leadership with the literature on women in leadership as a way of further exposing and understanding gendered organisational practices. Whilst the paper details only one women's experience it was through the connection to the literature that most "sense making" occurred and a realisation (on the part of one of the authors) that the experience was not unique or individualised but, rather, systematic of masculine, gendered, organisational cultures. The paper offers some "strategies for survival" for other women who may find themselves in similar situations. It concludes with a call for programs and strategies to bring about fundamental change. Although the setting is the higher education sector in Australia the paper's findings and recommendations have much broader applicability.